Valorisation of theanine from decaffeinated tea dust in bakery functional food. (2nd September 2014) - Culetu, Alina; Héritier, Julien; Andlauer, Wilfried
Summary Nowadays, consumers appreciate the positive properties of decaffeinated tea for their well‐being. During decaffeination process, a very fine tea dust powder is obtained as by‐product, which contains the same quantity of bioactives as decaffeinated tea: the antioxidant polyphenols and the amino acid theanine. The aim was to add value to theanine gained from black tea powder dust and to develop theanine‐enriched bread. A theanine containing powder was obtained by column separation of decaffeinated tea dust extract and spray‐drying using carrier supports. This powder contains also the very polar compounds from decaffeinated tea such as amino acids, sugars and minerals. Breads with 110, 220 and 330 ppm of theanine, respectively, were prepared with the theanine powder. Physical properties, theanine and total polyphenolic content in bread were analysed. Bread and other bakery food serve as good products to add value to bioactive tea dust ingredients.